HUBUNGAN KEAKTIFAN BELAJAR DENGAN CAPAIAN EVALUASI KOGNITIF PESERTA DIDIK PADA MATERI AKUNTASI PERUSAHAAN JASA - Habibullah, Habibullah; Genjik S, Bambang; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
Student Learning Activeness with the Achievement of Cognitive   Assessment of Class XII Students Accounting for Services   Company MA Darul Hidayah. The method used in this study uses   quantitative methods in the form of correlation or correlation   research. Data collection techniques using questionnaires,   unstructured interviews and documentaries. The tools used in data   collection are distributing questionnaires and documentation. The   sample used is saturated sampling technique involving all   correspondents. In this study, it was seen that there was a significant   relationship between learning activeness and the results of students'   cognitive evaluations which showed a correlation coefficient of   0.800. while the coefficient of determination in this study shows a   very significant relationship between learning activeness as   variable X and cognitive learning achievement as variable Y which   is equal to 0.722. When calculating the linear correlation, the   equation Y = 16.668 + 0.149 is obtained, which means that the   constant value is 16.668. If student learning activeness is worth 0,   then learning activeness is 0.149 which means an increase in   learning activeness by 1 will increase cognitive evaluation   achievement by 14.9%.